And which reader for which edition? (Prassi Ecdotiche della Modernità Letteraria, 2016)
Publishers are gradually focusing their attention on sorting out editions which are both readable by ‘common’ readers and textually correct, and both educational and with a grounded philological basis. They often use scholarly editions and specialized studies for educational editions, but they should develop a differentiated publishing policy, in order to give to the common reader comments and introductions whose aim should be to explain the original historical context of the work (which knowledge did authors presume from their contemporaneous readers?), the work’s fortune in times, and the complex evolution of the work, so as to arouse readers’ curiosity.
Keywords: philology; publishing; editorial practices; critical editions; scholarly editions; publishers; readers; Manzoni